The Evolution of Pesantren Education: Continuity and Change in Curriculum and Management amid Modernization - Mas'udi, Ahmad Thoyib (Lembaga Pengembangan Pesantren dan Diniyah Provinsi Jawa Timur, 2024)
Pesantren, Indonesia’s oldest Islamic educational institutions, have played a significant role in religious, social, and intellectual life for centuries. However, modernization and globalization have challenged their traditional frameworks. This study examines the evolution of pesantren education, focusing on continuity and change in curriculum and management while analyzing how pesantren adapt to contemporary demands without compromising their core values. Using a qualitative approach, the research employs historical analysis and field observations based on primary and secondary data. The findings reveal that pesantren have retained their emphasis on kitab kuning while integrating general and vocational subjects since the mid-20th century. Management practices have also shifted from centralized, kiai-led models to more participatory approaches. These changes are driven by community demands, government policies, and technological advancements. Although limited to a specific subset of pesantren, this study highlights their ability to balance tradition and innovation, demonstrating their potential as dynamic institutions capable of addressing contemporary educational and societal challenges.